2010
DOI: 10.1002/ajmg.b.31144
|View full text |Cite
|
Sign up to set email alerts
|

Gene–environment interactions in panic disorder and CO2 sensitivity: Effects of events occurring early in life

Abstract: Heterogeneous life events (LE) precede the onset of-and potentially increase the susceptibility to-panic disorder (PD). It remains unknown whether LE can act as moderators in the context of gene-by-environment interactions (G×E) that alter the susceptibility to PD and the related trait of CO₂ sensitivity, nor it is known whether such moderation may depend on occurrence of events at different epochs in life. In 712 general population twins we analyzed by Maximum Likelihood analyses of ordinal data whether life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 66 publications
2
39
0
Order By: Relevance
“…In particular, Roberson-Nay et al (2012a) showed that although PD and CSA share a common genetic diathesis, childhood environment adversities account for only 1.2% of adult-onset panic attacks. Conversely, however, Spatola et al (2011) found that early-life adversities do correlate with CO 2 hypersensitivity in adulthood provided that the stressful events took place before 18 years of age. Accordingly, the influence of the early-life adversities in the later development of PD remains unclear.…”
Section: Modelling the Comorbidity Of Panic Disorder With Childhood Smentioning
confidence: 85%
“…In particular, Roberson-Nay et al (2012a) showed that although PD and CSA share a common genetic diathesis, childhood environment adversities account for only 1.2% of adult-onset panic attacks. Conversely, however, Spatola et al (2011) found that early-life adversities do correlate with CO 2 hypersensitivity in adulthood provided that the stressful events took place before 18 years of age. Accordingly, the influence of the early-life adversities in the later development of PD remains unclear.…”
Section: Modelling the Comorbidity Of Panic Disorder With Childhood Smentioning
confidence: 85%
“…Battaglia et al reported three experiments [86][87][88] in which another variable was added to the twins' equation: the occurrence of traumatic events such as those leading to childhood separation anxiety, death of parents, and a history of generally stressful situations in childhood. The first of these, 86 with 700 twins, suggested the existence of a continuum of childhood separation anxiety and PD, and the association of both disorders with hypersensitivity to CO 2 .…”
Section: Twin Studiesmentioning
confidence: 99%
“…Following this report, a study of 712 subjects 87 concluded that the opposite could also be true: that ''genetic susceptibility to CO 2 response may influence the sensitivity to environmental hazard.'' The next trial, 88 also with 712 twins, suggested the existence of a relation between the occurrence of adverse life events, susceptibility to CO 2 , and later development of PD.…”
Section: Twin Studiesmentioning
confidence: 99%
“…The use of well-validated human endophenotypes that share part of the susceptibility with a corresponding diagnosis, but are at least partially independent of the clinical manifestation of the disorder, may become one "gold standard" in the field. These endophenotypes can be used as tools to investigate the mechanisms of illness while circumventing some of the limits connected with the inferential nature of behavioral testing (46,(72)(73)(74).…”
Section: Endophenotype Levelmentioning
confidence: 99%